2002
DOI: 10.1111/j.1348-0421.2002.tb02727.x
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae‐ and Candida albicans‐Derived Mannan Induced Production of Tumor Necrosis Factor Alpha by Human Monocytes in a CD14‐ and Toll‐Like Receptor 4‐Dependent Manner

Abstract: The cytokine‐inducing activities of fungal polysaccharides were examined in human monocytes in culture, with special reference to CD14 and Toll‐like receptors (TLRs). Tumor necrosis factor alpha (TNF‐α) production by monocytes was markedly induced in a dose‐dependent manner upon stimulation with cell walls from Candida albicans and mannan from Saccharomyces cerevisiae and C. albicans, although relatively high concentrations (10 to 100 μg/ml) of stimulants were required for activation as compared with the refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(175 citation statements)
references
References 62 publications
8
159
2
6
Order By: Relevance
“…To investigate the receptors involved in NADPH oxidase activation, DC were stimulated with purified biglycan, glucan and Pam 3 CSK4, specific agonists of CD206, dectin-1 and TLR2, respectively [44][45][46]. We found that biglycan and Pam 3 CSK4, alone or in combination, did not activate ROS production (Fig.…”
Section: Dectin-1 Mediates Nadph Oxidase Activationmentioning
confidence: 89%
“…To investigate the receptors involved in NADPH oxidase activation, DC were stimulated with purified biglycan, glucan and Pam 3 CSK4, specific agonists of CD206, dectin-1 and TLR2, respectively [44][45][46]. We found that biglycan and Pam 3 CSK4, alone or in combination, did not activate ROS production (Fig.…”
Section: Dectin-1 Mediates Nadph Oxidase Activationmentioning
confidence: 89%
“…that are sensed by dendritic cells. TLRs have been implicated in the sensing of fungal polysaccharides by monocytes (8,9) and dendritic cells (10). However, there are very few examples in which the TLR involved in fungal polysaccharide recognition has been characterized (11).…”
mentioning
confidence: 99%
“…70 TLR2 and TLR4 are the most well characterized of the TLRs with respect to their involvement in fungal recognition. TLR4, which is expressed on the surface of macrophages, DCs, and endothelial cells, 71,72 recognizes C. albicans-derived mannan, 73 possibly in conjunction with the CD14 receptor. It is involved in the control of fungal replication in the kidneys, likely by inducing the secretion of CXC cytokines such as KC and MIP-2, which subsequently recruit neutrophils to the site of infection.…”
Section: Deficiencies Of Innate Immunity and Involvement In Early Infmentioning
confidence: 99%